On Three Poems by Luis Alberto de Cuenca: between Rewriting and Variation - Suárez Martínez, Luis Miguel (Dicenda. Estudios de lengua y literatura españolas, 2023)
The poem “Ἔρως ἀνίκατε μάχαν”, which appeared in the anthology Espejo del amor y de la muerte (1971), was not later included by Luis Alberto de Cuenca in Elsinore. To explain this exclusion, it may be pertinent to analyze its thematic and formal parallels with two other poems from that book: "Desitjada mort" and "Love’s Labour’s lost". The analysis, which extends to the lexical level, reveals such close connections that they can be considered as variations on the same topic —like an elegiac triptych inspired by the memory of the dead beloved— or even, in the case of the first two, as successive versions of the same poem.